2013
DOI: 10.1007/s10071-013-0598-y
|View full text |Cite
|
Sign up to set email alerts
|

Implicit chaining in cotton-top tamarins (Saguinus oedipus) with elements equated for probability of reinforcement

Abstract: Three experiments examined the implicit learning of sequences under conditions in which the elements comprising a sequence were equated in terms of reinforcement probability. In Experiment 1 cotton-top tamarins (Saguinus oedipus) experienced a five-element sequence displayed serially on a touch screen in which reinforcement probability was equated across elements at .16 per element. Tamarins demonstrated learning of this sequence with higher latencies during a random test as compared to baseline sequence train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…It has already been shown that monkeys can learn regular patterns within the serial RT paradigm by displaying faster RTs after sufficient exposure to these patterns (Heimbauer et al, 2012;Locurto et al, 2010Locurto et al, , 2013Procyk et al, 2000). Several attempts have even been made to study the learning of non-adjacent dependencies (Newport, Hauser, Spaepen, & Aslin, 2004) and monkeys' sensitivity to the grammar of human natural language (Saffran et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been shown that monkeys can learn regular patterns within the serial RT paradigm by displaying faster RTs after sufficient exposure to these patterns (Heimbauer et al, 2012;Locurto et al, 2010Locurto et al, , 2013Procyk et al, 2000). Several attempts have even been made to study the learning of non-adjacent dependencies (Newport, Hauser, Spaepen, & Aslin, 2004) and monkeys' sensitivity to the grammar of human natural language (Saffran et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cotton-top tamarins were able to discriminate a word from a non-word or a part-word after having been exposed to an artificial language in a protocol similar to Saffran (Hauser, Newport, & Aslin, 2001). Moreover, experiments using the serial response time task (SRT; Nissen & Bullemer, 1987), a task in which a participant have to respond to sequences of stimuli that appear one-by-one at various locations on a computer screen, showed that non-human primates can also use statistical cues to learn a predictable motor sequence (Heimbauer, Conway, Christiansen, Beran, & Owren, 2012;Locurto, Dillon, Collins, Conway, & Cunningham, 2013;Locurto, Gagne, & Nutile, 2010;Procyk, Ford Dominey, Amiez, & Joseph, 2000). On these grounds, we chose to test a group of Guinea baboons (Papio papio) instead of humans.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we did not include any intertrial interval between stimuli or between repetitions of the sequence, whereas tamarin monkeys received a 5‐s white screen prior to the first element in a chain and a 20‐second black screen following the final element (Locurto et al, , , & Experiment 1 of 2013), or a 1‐s ITI between every pair of elements (Locurto et al, , Experiment 2). It could be that forcing subjects to pause between responses encouraged perceptual encoding of the responses.…”
Section: Discussionmentioning
confidence: 99%
“…All three subjects had served previously in implicit-learning experiments (viz. Locurto et al, 2013;Locurto et al, 2009;Locurto et al, 2010). The tamarins were born and housed individually at the New England Primate Research Center, Southborough, Massachusetts, and were maintained under the guidelines of the Committee on Animals of the Harvard Medical School.…”
Section: Subjectsmentioning
confidence: 99%
“…Two subsequent series of studies using tamarins have extended this basic procedure (Locurto, Dillon, Collins, Conway, & Cunningham, 2013;Locurto et al, 2010). These studies revealed that, in the format of presenting elements in an A → E pattern with reinforcement at the end of the chain, a visually based task in which the elements were defined as different images rather than as different spatial locations of the same image produced approximately the same levels of implicit learning (Locurto et al, 2010, Exp.…”
mentioning
confidence: 99%